Specialist tool for monitoring the measurement degradation process of induction active energy meters - Silva, M. R. [UNESP]; Galotto, L. [UNESP]; Pinto, J. O P; Canesin, C. A. [UNESP]; Cardoso, E. H.; Amorim, S.; Mertens, E. A. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This paper presents a methodology and a specialist tool for failure probability analysis of induction type watt-hour meters, considering the main variables related to their measurement degradation processes. The database of the metering park of a distribution company, named Elektro Electricity and Services Co., was used for determining the most relevant variables and to feed the data in the software. The modeling developed to calculate the watt-hour meters probability of failure was implemented in a tool through a user friendly platform, written in Delphi language. Among the main features of this tool are: analysis of probability of failure by risk range; geographical localization of the meters in the metering park, and automatic sampling of induction type watt-hour meters, based on a risk classification expert system, in order to obtain information to aid the management of these meters. The main goals of the specialist tool are following and managing the measurement degradation, maintenance and replacement processes for induction watt-hour meters. © 2011 IEEE.
Keywords: Artificial intelligence; Expert system for sampling; Hazard rate; Induction type Watt-hour meters; Risk Model; Active energy; Automatic sampling; Degradation process; Delphi language; Distribution companies; Failure Probability; Probability of failure; Risk classification; User-friendly platforms; Degradation; Electricity; Expert systems; Information management; Instruments; Risk assessment; Measurements